Trust in Institutions and Tax Compliance. A Multilevel Analysis of the Regions of Spain - Cantero-Galiano, Jesús (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis: The aim of this work is to delve into the significance of trust in the phenomenon of tax compliance. Specifically, the relationship between taxpayers’ trust in the Government, administrations and institutions and their reported disposition towards tax compliance is explored based on the case of Spain and at regional level (NUTS2). Methodology: Using 2017 data collected by the European Values Study (EVS) and the Quality of Government Institute at the University of Gothenburg (QoG), a multilevel linear model is proposed where we assess the impact of citizen support for the Government and institutions on the disposition towards tax compliance. This model allows to simultaneously capture the relationships at taxpayer level and the effects of regional factors in the same equation. Results of the research: The results of the multilevel estimation allow the authors to reject the null hypothesis and accept, at least provisionally, the existence of a direct effect of trust in the institutions on tax compliance at regional level. Additionally, the low significance observed in the regional level variables suggests that citizens have non-decentralized perception of tax obligations. Furthermore, given that the effects are measured in terms of the quality of the institutions and government, the implications for regional policy and the actions of regional governments are of significant interest for the study of tax behavior and compliance.